Narrative of a Voyage round the World In the Uranie and Physicienne Corvettes, Commanded by Captain Freycinet, during the Years 1817, 1818, 1819, and 1820 - Arago, Jacques 1790-1855 (Cambridge library collection. Maritime exploration, 1823)
Founded in 1666, the French Académie des Sciences was a prominent and prestigious organisation behind numerous scientific advances in Europe in the seventeenth and eighteenth centuries. In 1817, commissioned by the Académie, Louis de Freycinet (1779–1841) embarked on a three-year expedition with the main purpose of investigating terrestrial magnetism and taking a series of pendulum measurements. In the course of this voyage around the world, the scientists aboard the Uranie also collected an abundance of samples and made significant observations in the fields of geography, ethnology, astronomy, hydrography and meteorology. The progress of this journey was detailed by Jacques Arago (1790–1855), draughtsman on the expedition, in the form of letters to a friend. This illustrated narrative is prefaced by a report to the Académie which summarises the mission's findings. Translated into English and published in 1823, this work is an informative and often witty account, reflecting contemporary ambitions in science and exploration